CYTOTOXIC ACTIVITY OF ANREDERA CORDIFOLIA LEAF EXTRACT ON HELA CERVICAL CANCER CELLS THROUGH p53-INDEPENDENT PATHWAY - Yuliani, Sri Hartati; Anggraeni, Clara Dewi; Sekarjati, Winda; Panjalu, Andung; Istyastono, Enade Perdana; Setiawati, Agustina (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: This study investigated cytotoxic activity and apoptosis induction of Anredera cordifolia leaf extract on cervical cancer cells. Methods: A. cordifolia leaf extract was prepared by maceration using 70% ethanol. This study used HeLa cells, a model of stress inducing-p53 cervical cancer cells. Cytotoxic study on HeLa cells was designed by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyltetrazolium bromide (MTT) test, further apoptotic induction assay was determined by annexin V-FITC method. Molecular mechanism of the extract on HeLa was assayed by p53 immunocytostaining. The MTT data were analyzed using linear regression to get IC50 then apoptosis was conducted by ModFit LT and immunocytochemistry data were qualitatively analyzed. Results: A. cordifolia leaf extract showed cytotoxic activity and promoted apoptosis in HeLa cells with IC50 value 75 Î¼g/mL. The extract did not increase level expression of p53 in cells. Conclusion: Cytotoxic activity of A. cordifolia leaf extract on HeLa cells was through a p53-independent pathway. Keywords: Anredera cordifolia, Apoptosis, Cervical cancer, p53.